Pengaruh Implementasi Pendekatan Keterampilan Proses Terhadap Hasil Belajar IPS di SD Kecamatan Sukasada - Komang Surya Adnyana; Gusti Ngurah Arya Yudaparmita (Edukasi: Jurnal Pendidikan Dasar, 2022)
Education is the spearhead of the progress of a nation. Education is an effort that is deliberately designed to achieve the goals that have been set. Education aims to improve the quality of human resources. One of the efforts to improve human resources is through the quality of the learning process in schools. Efforts to improve an education require a long time, an orderly and systematic process, because it is related to various aspects of the life of the quality of education, because it is adapted to the times, for example about educational autonomy, community needs, and the spirit of regional autonomy in managing human resources in the future. front. Approaches in learning are very important to do so that the learning process becomes more creative and innovative. In the social studies learning process so far, teachers apply the classical approach and the lecture method is the main choice in learning.